2 - Education des filles: Quelles perspectives pour l'Afrique subsaharienne au XXIe siècle? by Alphonsine Bouya - Alphonsine Bouya, (Africa Development, 1994)
Education for girls in Africa has become a meg or item on the agenda cf international organisations, African governments and non-governmental organisations operating both within and outside Africa At many meetings, the meg or bottlenecks have been identified and suggestions made as to how to enhance women's participation in development through improved educational system The major result is that women must be less and less marginalised That can be achieved only through imposing the quality of women's education and eradicating the injustice and the inequality women are facing. The actions which must liberate women and free their energy must come from everybody, i.e. governments, the population itself, scholars and the international community. These actions should include increasing the number of girls enrolled in school mostly in science and technology, expanding formal education to all (bays and' girls), harmonising formal, non-formal and informal educational systems, increasing the number of trainers and teachers, enhancing the skills of educational planners, creating new and less-gender biased evaluation systems etc.